Long-term undiagnosed tuberous sclerosis - Tatyana N. Varenova; Venera A. Goshadze; Daria I. Akutina; Oleg N. Pomerantsev (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
The article presents the history, etiology, pathogenesis and variability of the clinical picture of a rare genetic disease tuberous sclerosis. The clinical and laboratory criteria on the basis of which this diagnosis is made are described. Specialists of the Nizhny Novgorod Branch of the State Research Center of Dermatovenereology and Cosmetology, Ministry of Health of the Russian Federation carried out treatment and observation of the patient K. Patient was born in 1997, repeatedly turned to dermatologists in different cities of Russia with complaints about formations on the face, hands, legs and spots on the skin of the trunk that appeared in early childhood. The diagnosis was not confirmed. The doctors of the consultative and diagnostic center diagnosed with tuberous sclerosis based of four large and two small diagnostic criteria. Treatment of skin manifestations was carried out by laser destruction, it gave a good cosmetic effect. We recommended further examination by doctors of related specialties for identify lesions of other organs. This clinical case is of interest for dermatologists, because the described dermatosis is rarely found in everyday practice.